Micromorphology of modern tills in southwestern Spitsbergen – insights into depositional and post-depositional processes - Skolasińska, Katarzyna; Rachlewicz, Grzegorz; Szczuciński, Witold (Polish Polar Research, 2016)
Abstract Textural properties and microstructures are commonly used properties in the analysis of Pleistocene and older glacial deposits. However, contemporary glacial deposits are seldom studied, particularly in the context of post-depositional changes. This paper presents the results of a micromorphological study of recently deposited tills in the marginal zones of Hansbreen and Torellbreen, glaciers in southwestern Spitsbergen. The main objectives of this study were to compare modern tills deposited in subglacial and supraglacial conditions, as well as tills that were freshly released from ice with those laid down several decades ago. The investigated tills are primarily composed of large clasts of metamorphic rocks and represent coarse-grained, matrix-supported diamictons. The tills reveal several characteristic features for ductile ( e.g. turbate structures) and brittle ( e.g. lineations, microshears) deformations, which have been considered to be indicative of subglacial conditions. In supraglacial tills, the same structures are common as in the subglacial deposits, which points to the preservation of the primary features, though the sediment was transferred up to the glacier surface due to basal ice layer deformation and redeposited as slumps, or to formation of similar structures due to short-distance sediment re-deposition by mass flows. This study revealed that it might not be possible to distinguish subglacial and supraglacial tills on the basis of micromorphology if the latter are derived from a subglacial position. The only noted difference was the presence of iron oxide cementation zones and carbonate dissolution features in supraglacial tills. These features were found in tills that were deposited at least a few years ago and are interpreted to be induced by early post-depositional processes involving porewater/sediment interactions.